2011
DOI: 10.1177/155005941104200409
|View full text |Cite
|
Sign up to set email alerts
|

A Brain-Computer Interface as Input Channel for a Standard Assistive Technology Software

Abstract: Recently brain-computer interface (BCI) control was integrated into the commercial assistive technology product QualiWORLD (QualiLife Inc., Paradiso-Lugano, CH). Usability of the first prototype was evaluated in terms of effectiveness (accuracy), efficiency (information transfer rate and subjective workload/NASA Task Load Index) and user satisfaction (Quebec User Evaluation of Satisfaction with assistive Technology, QUEST 2.0) by four end-users with severe disabilities. Three assistive technology experts evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
147
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(157 citation statements)
references
References 30 publications
2
147
0
Order By: Relevance
“…It may be acceptable to patients if the time needed to select a symbol or make a decision (e.g., yes or no) is in the order of minutes. In principle, detecting focused attention on one of the streams is sufficient to realize an ssBCI and thus, to control any kind of AT software or device that can be controlled by simple binary yes/no commands [15]. Therefore, since single-trial classification was not successful in patients but significant effects were found on average only, future modifications of the paradigm should aim at signal processing and classification methods involving averaging of many data segments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be acceptable to patients if the time needed to select a symbol or make a decision (e.g., yes or no) is in the order of minutes. In principle, detecting focused attention on one of the streams is sufficient to realize an ssBCI and thus, to control any kind of AT software or device that can be controlled by simple binary yes/no commands [15]. Therefore, since single-trial classification was not successful in patients but significant effects were found on average only, future modifications of the paradigm should aim at signal processing and classification methods involving averaging of many data segments.…”
Section: Discussionmentioning
confidence: 99%
“…Both requirements can be fulfilled by using a single-switch BCI (ssBCI) which reliably detects one specific brain pattern of the patient [13,14]. Consequently, any kind of assistive technology (AT) can be controlled by simple binary yes/no commands provided by the ssBCI [15].…”
Section: Introductionmentioning
confidence: 99%
“…Important factors in this include the patient's physical independence (defined as the physical and/or cognitive ability to fulfill tasks), and self-care management (defined as access to and the ability to use and control devices/resources supporting living in the community regardless of the patient's level of physical ability) [7]. Recent reports have shown that emerging technologies (technical innovations) may significantly and positively influence disabled people's quality of life [8][9][10][11].…”
Section: Integrated It Environments For People With Disabilities: Thementioning
confidence: 99%
“…Numerous applications have been proven to work with various BCI paradigms such as spelling [7], Internet browsing [8], entertainment [9], environmental control [10], gaming [11][12], neuroprostheses [13], wheelchair control [14] and cognitive rehabilitation [15]. It is evident that BCI can now control a number of applications however little evidence of this is present beyond the laboratory and limited evaluations have been undertaken with participants that would benefit from the use of such a system on a daily basis.…”
Section: Introductionmentioning
confidence: 99%